2012
DOI: 10.1177/0363546512446681
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Anterior Glenoid Bone Defects in Posttraumatic Recurrent Anterior Shoulder Instability Using the J-Bone Graft Shows Anatomic Graft Remodeling

Abstract: Anatomic glenoid reconstructive surgery using the J-bone graft technique benefits from a physiological remodeling process, molding the bone graft closely into the original shape of an uninjured anterior glenoid rim. While parts of the graft lying inside the projected former surface area of the glenoid are preserved, the parts lying outside are resorbed over time, suggestive of strain-adapted graft remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
48
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 19 publications
(43 reference statements)
1
48
2
1
Order By: Relevance
“…Although the BSSR remains a mere approximation of the highly complex and multifactorial true shoulder stability ratio, it allows for simple determination of the bony stability of a shoulder based on CT scans, which might improve preoperative evaluation of inherent or post-traumatic bony glenoid concavity deficiencies or postoperative determination of the achieved stabilizing effect by different bone grafting techniques including bone graft remodeling processes over time. 16 Limitations A limitation of our study is the fact that the distinction between traumatic and atraumatic anterior shoulder instability can sometimes be difficult, especially because the transition comprises a certain gray area, which possibly might have resulted in the misplacement of single patients in the wrong instability group. Another limitation is the possibility of asymmetry between the glenoid concavities within a patient, which cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Although the BSSR remains a mere approximation of the highly complex and multifactorial true shoulder stability ratio, it allows for simple determination of the bony stability of a shoulder based on CT scans, which might improve preoperative evaluation of inherent or post-traumatic bony glenoid concavity deficiencies or postoperative determination of the achieved stabilizing effect by different bone grafting techniques including bone graft remodeling processes over time. 16 Limitations A limitation of our study is the fact that the distinction between traumatic and atraumatic anterior shoulder instability can sometimes be difficult, especially because the transition comprises a certain gray area, which possibly might have resulted in the misplacement of single patients in the wrong instability group. Another limitation is the possibility of asymmetry between the glenoid concavities within a patient, which cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the early contact forces on the bone graft are useful for graft integration and for the prevention of excessive graft resorption, which has been explained by Frost et al [19]. As Moroder et al observed, bone grafts that are used for the reconstruction of the glenoid are subject to an anatomical remodelling process [20]. Accordingly, we observed that the compression of the humeral component on the graft, which was exerted by the musculature, formed a new concavity that facilitated the subsequent glenoid-component implantation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to patients with an Glenoid loosening 120 98 TSA 7 42 2 8 F, 80 Glenoid loosening 96 111 TSA 18 44 2 9 F, 79 Glenoid loosening 60 95 TSA 26 47 4 11 M, 65 Glenoid loosening 180 97 TSA 29 50 5 12 M, 74 Glenoid loosening 72 102 TSA 28 71 4 15 M, 74 Glenoid loosening 168 150 TSA 53 75 8 5 F, 53 Glenoid loosening 36 126 TSA 24 50 2 [14]. Correction of the version by reaming has been shown to have a limit of approximately 15° [5,13,20]. In a biomechanical study, Shapiro et al found that a glenoid component retroversion of 15°significantly affected the glenohumeral contact area and led to increased contact pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Besondere Beachtung ist unabhängig vom Operationsverfahren der Positionierung des Transplantats zu schenken, wobei die Beziehung zur Gelenkfläche als entscheidender Faktor gilt. So konnte festgestellt werden, dass eine physiologische Remodellierung des Spans stattfindet, sofern der Span adäquaten Kontakt zum Humeruskopf erlangt [31]. Nichtbelastete Anteile werden dabei resorbiert, so dass nach abgeschlossenem Umbauprozess etwa die Fläche des unversehrten Glenoids resultiert.…”
unclassified